(3ecGJHI JPcQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3cJGHi Edi Cgdi hENhGfi GdHQQI GdSGObjf hGdCUajGA GdWgQI hGdeMbbjf CPcGQ Gdef JPcQh OYi heMLI def aGA Edi GdMb s
(3BNQgG (B:s
(3hGYdehG Cfg dGTjN dce hdGQFjS Ydjce hdG CeQ dCMO ef GdCfGe EdG HeG jWGHb GdMb hGdMeO dehdGfG hMOg hGdTcQ dhdjg GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B91s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis